Accessing a high‐voltage nonaqueous hybrid flow battery with a sodium‐methylphenothiazine chemistry and a sodium‐ion solid electrolyte. Issue 1 (1st September 2021) - Yu, Xingwen; Manthiram, Arumugam
Abstract: The development of redox flow batteries (RFBs) with nonaqueous electrolytes offers the possibility of accessing a high cell‐operation voltage (no restrain of hydrogen evolution and oxygen evolution potentials) and a low operation temperature (can be operated below the freezing point of water). Therefore, nonaqueous RFBs have recently garnered increasing attention. However, the cross‐mixing of liquid electrode/electrolyte materials has been plaguing the progress of the nonaqueous RFBs. Herein, we present a crossover‐free, high voltage nonaqueous hybrid flow battery (HFB) with a novel sodium‐methylphenothiazine (MPT) chemistry and a single‐ion solid‐electrolyte separator. The Na‐MPT redox couple delivers a high voltage of ~2.6 V when the cell was operated at a medium current density. A NASICON‐type solid electrolyte membrane (Na3 Zr2 Si2 PO12 ) could circumvent the crossover of the liquids between the positive and negative electrodes, and meanwhile could maintain a single‐ion (Na + ‐ion) conduction between the two electrodes to sustain the electrochemical reactions. Under such an electrochemical mechanism, the nonaqueous Na‐MPT HFB shows remarkable cycling performance. Abstract : A crossover‐free, high voltage nonaqueous hybrid flow battery (HFB) is developed with a novel sodium‐methylphenothiazine (MPT) chemistry and a single‐ion solid‐electrolyte separator.